2000
DOI: 10.1890/0012-9615(2000)070[0423:lsdaci]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Landscape-Scale Disturbances and Changes in Bird Communities of Boreal Mixed-Wood Forests

Abstract: Bird community response to both landscape‐scale and local (forest types) changes in forest cover was studied in three boreal mixed‐wood forest landscapes modified by different types of disturbances: (1) a pre‐industrial landscape where human settlement, agriculture, and logging activities date back to the early 1930s, (2) an industrial timber managed forest, and (3) a forest dominated by natural disturbances. Birds were sampled at 459 sampling stations distributed among the three landscapes. Local habitat and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
165
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 207 publications
(179 citation statements)
references
References 71 publications
11
165
2
1
Order By: Relevance
“…These new patches would thus favour open-habitat species Kelly et al 2014) and associated ecosystem services (Whelan et al 2008). We also suggest that further funding of sustainable forest harvesting should be considered in the study area to offset the loss of open habitats and to prevent the occurrence of high-intensity fires as a result of fuel accumulation (Stephens 1998;Drapeau et al 2000;King et al 2011;Fenton et al 2013).…”
Section: Strengths and Weaknesses Of Rewilding: Implications For Consmentioning
confidence: 88%
“…These new patches would thus favour open-habitat species Kelly et al 2014) and associated ecosystem services (Whelan et al 2008). We also suggest that further funding of sustainable forest harvesting should be considered in the study area to offset the loss of open habitats and to prevent the occurrence of high-intensity fires as a result of fuel accumulation (Stephens 1998;Drapeau et al 2000;King et al 2011;Fenton et al 2013).…”
Section: Strengths and Weaknesses Of Rewilding: Implications For Consmentioning
confidence: 88%
“…Stand composition: conifer vs. beech Although some studies have identiWed little impact of tree species composition on bird communities (Müller 1987;Patterson et al 1995;Donald et al 1998), most authors have found, as we have, a greater diversity in broadleaf forests compared with coniferous forests of similar stages, at plot level (Moss 1978;James and Wamer 1982;Bibby et al 1985;Lebreton and Choisy 1991;Baguette et al 1994;Solonen 1996;Gjerde and Saetersdal 1997) as well at larger levels including the whole silvicultural cycle (Jokimäki and Huhta 1996;Drapeau et al 2000). Conifer forests seem to attract only few bird species, as suggested by Drapeau et al (2000).…”
Section: Discussionmentioning
confidence: 45%
“…Conifer forests seem to attract only few bird species, as suggested by Drapeau et al (2000). In the Ardenne region, the total bird species richness in mature conifer plantation is estimated to be 43 species with a mean richness per plot of 13 species, while the estimations for beech forests are 44 species for the total richness and 16 species for the mean richness per plot (Paquet et al 2006).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, any large-scale spatial scenario should ideally maximize the amount of oldgrowth forest, which is generally rarified by forestry practices that harvest trees at maturity (i.e., between 60 and 100 years of age in Quebec) rather than waiting for trees to begin to die and stands structure to become less uniform. The structurally diverse, deadwood-rich, old-growth stands that are often not allowed to develop in a managed forest are important for many species of plants and animals in the boreal forest of Quebec as elsewhere (e.g., Imbeau et al Environmental Management 2000;Drapeau et al 2000Drapeau et al , 2003Boudreault et al 2002;Desponts et al 2002Desponts et al , 2004Fenton and Bergeron 2008). In the interest of maintaining as much habitat for as many native species as possible, stand diversity should also be maintained.…”
Section: Introductionmentioning
confidence: 99%